International Delphi survey of the ESTS/AATS/ISTH task force on venous thromboembolism prophylaxis in thoracic surgery: the role of extended post-discharge prophylaxis. (26th November 2019) - Agzarian, John; Litle, Virginia; Linkins, Lori-Ann; Brunelli, Alessandro; Schneider, Laura; Kestenholz, Peter; Li, Hui; Rocco, Gaetano; Girard, Philippe; Nakajima, Jun; Samama, Charles Marc; Scarci, Marco; et al.
Abstract: OBJECTIVES: Venous thromboembolic events can be successfully prevented with chemical and/or mechanical prophylaxis measures, but evidence-based guidelines in thoracic surgery are limited, particularly regarding extended post-discharge prophylaxis. This study attempts to gather an international consensus on best practices to inform the development of such guidelines. METHODS: A series of 3 surveys was distributed to the ESTS/AATS/ISTH (European Society of Thoracic Surgeons, American Association of Thoracic Surgeons, International Society for Thrombosis and Haemostasis) venous thromboembolic events prophylaxis working group starting January 2017. This iterative Delphi consensus process sought to gather a consensus on (i) risk factors; (ii) preferred agents; (iii) duration; and (iv) perceived barriers to an extended thromboprophylaxis approach. Participant responses were expressed on a 10-point scale, and the results were summarized and circulated to all respondents in subsequent rounds. A coefficient of variance of ≤0.3 was identified pre hoc to identify agreement. RESULTS: A total of 21 Working Group members completed the surveys, composed of 19% non-surgeon thrombosis experts, and 48% from North America. Respondents largely saw agreement regarding risk factors that indicate a need for extended thromboprophylaxis. The group agreed that low-molecular-weight heparin is a suitable agent for use post-discharge, but there was a wide variety in response regarding agents, duration and barriers to extended prophylaxis, where no consensus was observed across the three rounds. CONCLUSIONS: There is strong agreement around indications for extended venous thromboembolic events thromboprophylaxis after thoracic surgery, but there is little consensus regarding the agents and duration to be employed. Further research is required to better inform guideline development.